When opportunity meets ability: The moderating effects of prolific inventors on novel drug innovation following product development failure in biotechnology - Tzabbar, Daniel; Lahiri, Amrita; Seo, Donghwi Josh; Boeker, Warren (Strategic Management Journal, 2023)
Abstract Research Summary Through a longitudinal study of the product development portfolios of 457 US‐based firms in the biotechnology industry, we investigate how prolific inventors shape a firm's innovative direction following product development failure. Contrary to received wisdom, we argue and demonstrate that an increase in the number of prolific inventors is associated with a decrease in firm propensity to pursue novel product innovation following such failure. We further find that the presence of prolific inventors with greater collaborative strength and longer tenure negatively moderate the positive relationship between failure and the pursuit of novel product development. We discuss the implications of our results for research on learning from failure and strategic human capital. Managerial Summary In case of adverse events such as product development failure, managers often rely on the firm's prolific inventors to help the firm learn from failure. Our study shows that there are limits to this approach. While prolific inventors increase firm propensity for novel product development, such propensity is significantly decreased following product failure. We further establish that the presence of prolific inventors with greater collaborative strength and long tenures is especially likely to reduce firms' pursuit of novel products, while the presence of those with low collaborative strength and tenure tend to increase this propensity.